CLINICAL AND SUBCLINICAL CHARACTERISTICS IN CHILDREN WITH THALASSEMIA AT QUANG NGAI HOSPITAL FOR WOMEN AND CHILDREN (Vietnam Journal of Community Medicine, 2022)
Background: Thalassemia belongs to the group of congenital hemolytic diseases, monogenicinheritance, and recessive character. Hemoglobin electrophoresis helps in the diagnosis of thisdisease. This technique has been put into operation at Quang Ngai Hospital for Children andWomen since January 2021, helping in the diagnosis and treatment of Thalassemia in their homeprovince as well as reducing the difficulty in monitoring and medical treatment cost for patients.There hasn’t been a study on Thalassemia in Quang Ngai yet. We study to evaluate the clinical andsubclinical characteristics of children with Thalassemia.Objective:To describe some clinical and subclinical characteristics according to disease form in childrenwith Thalassemia at Quang Ngai Hospital for Women and Children.Method:A descriptive cross-sectional study on 64 children diagnosed with Thalassemia at Quang NgaiHospital for Women and Children from January 2021 to September 2021.Result:Clinical characteristics: The mean age is 3.5±2.9 years, the age group from 2 to under 5 yearsold accounts for 46.9%. The rate of male/female is 1.46/1, its proportion in rural areas is more thanin urban areas. The majority of children in the study are the Kinh, accounting for 78.1%. Amongthem, 20 children admitted to the hospital for check-ups account for 31.3%, 15 children with paleskin account for 23.4% and the lowest rate is diarrhea with 2 children, accounting for 3.1%. Inchildren with skin symptoms, pale mucous membranes reach 62.5%, there is no case of dark skinand black gums. Most of the children in the study group are α-Thalassaemia hidden, accountingVietnam Journal of Community Medicine, Vo;FILE MẪU 241for 60.9%. There is no difference in the distribution of disease by gender and ethnicity, withp>0.05.Subclinical characteristics: The average Hb 9.4±1.6g/dl. The mean MCH, MCV and RDW are20.4±2.9pg, 68±8.1fL, 17.3±0.1%, respectively. The average serum iron concentration is 12.8 ±6.3µmol/l (min: 1.6µmol/l, max: 30.6µmol/l). The average ferritin concentration is 147.1 ±133.5µmol/l (min: 33.2ng/dl, max: 694.6ng/dl).Electrophoresis result: In mild α-Thalassaemia, all patients have HbA over 95.2%, mean 96.9%,HbA2 under 3.5%, mean 2.4%, mean HbF is 1.1%. In HbH, the mean value of HbA is 83.4%,1.7% HbA2 and 1.3%HbF, there is a present of HbH, with an average value of 10.7%. In bThalassaemia, the mean value of HbA is 85.0%, the mean value of HbA2 is 3.0% (min:1.3%, max:6.1%), the mean value of HbF is 10.8% (min:1.5%, max: 64.2%). In b-Thalassaemia/HbE, 67.7%HbA, 3.56% HbA2, 12.3% HbF, there is a present of HbE, with an average value of 28.04%.Conclusion: Thalassemia is a congenital hemolytic disease with autosomal recessiveinheritance. The percentage of Vietnamese people carrying the Thalassemia gene is high. Thedisease has a variety of clinical manifestations, from no clinical symptoms to severe clinicalsymptoms, such as anemia, hepatosplenomegaly, bone deformities, etc. Hemoglobinelectrophoresis test contributes to the diagnosis. diagnose thalassemia.The proportion of Thalassemia gene is high. This disease has diverse clinical symptoms, fromno clinical symptoms to severe clinical symptoms, such as anemia. Hemoglobin electrophoresiscontributes to the diagnosis of Thalassemia.
Keywords: Thalassemia, Congenital hemolytic disease, Hemoglobin Electrophoresis, Quang Ngai Hospital for Women and Children.